(untitled) (International Seven Journal of Health Research, 2024)
Inflammatory bowel disease (IBD) is an immune-mediated disorder of the gastrointestinal tract, encompassing chronic conditions resulting in inflammation in the region. Its prototypical forms, Crohn’s Disease (CD) and Ulcerative Retocolitis (UC), are influenced by genetic-environmental interactions, and their incidence has shown an increase due to the westernization of dietary patterns, registering around 7 million cases in 2017. Both CD and RU are characterized by chronic inflammation, and CD can affect any part of the gastrointestinal tract, from the mouth to the anus, with intermittent inflammation prone to complications such as stenosis and fistulas. RU, on the other hand, predominantly affects the colon and rectum, exhibiting continuous inflammation that can culminate in ulcers and bleeding.